Dose-dependent pain and pain radiation after chemical stimulation of the thoracolumbar fascia and multifidus muscle: a single-blinded, cross-over study revealing a higher impact of fascia stimulation - Vogel, Simon; Magerl, Walter; Treede, Rolf-Detlef; Schilder, Andreas (Life, 2022)
Acute low back pain can be experimentally induced by injections of hypertonic saline into deep tissues of the back, such as fascia and muscle. The current study investigated the dose-dependency of peak-pain and spatial extent of concomitant radiating pain following 50, 200 and 800 μL bolus injections of hypertonic saline (5.8%) into the thoracolumbar fascia and multifidus muscle, since data on dose-dependency is lacking in humans. Sixteen healthy subjects rated (11 female, 5 male; 23.3 ± 3.1 years, mean ± SD) intensity and spatial extent of pain. Injections into the fascia resulted in significantly higher peak-pain (+86%, p < 0.001), longer pain durations (p < 0.05), and larger pain areas (+65%, p < 0.02) and were less variable than intramuscular injections. Peak-pain ratings and pain areas were 2-3-fold higher/larger for 200 μL vs. 50 μL. In contrast, peak pain increased only marginally at 800 μL by additional 20%, while pain areas did not increase further at all in both, fascia and muscle. Thus, higher injection volumes did also not compensate the lower sensitivity of muscle. Peak-pain ratings and pain areas correlated between fascia and muscle (r = 0.530, p < 0.001 and r = 0.337, p < 0.02, respectively). Peak-pain ratings and pain areas correlated overall (r = 0.490, p < 0.0001), but a weak correlation remained when the impact of between-tissue differences and different injection volumes were singled out (partial r = 0.261, p < 0.01). This study shows dose-dependent pain responses of deep tissues where an injection volume of 200 μL of hypertonic saline is deemed an adequate stimulus for tissue differentiation. We suggest that pain radiation is not simply an effect of increased peripheral input but may afford an individual disposition for the pain radiation response. Substantially higher pain-sensitivity and wider pain areas support fascia as an important contributor to non-specific low back pain.
Gesehen am 29.04.2024